Hypoxia-Preconditioned MSCs for Enhanced Bone Regeneration in Ovine Fracture Case - Okky Ardianto; Berlian Ramadhanti (Stem Cell and Cancer Research (SCCR), 2025)
Background: Bone fracture is a common clinical issue that occurs in humans and animals. The fracture-wound healing process may have a variable duration since several conditions interfere with tissue regeneration. Mesenchymal stem cells (MSCs)-based therapy offers regenerative potential. Objective: This study aimed to evaluate the therapeutic effects of hypoxia umbilical cord mesenchymal stem cell (UC-MSC) secretome on fracture wound healing in sheep. Methods: A one-year-old male thin-tailed sheep (Ovis aries) weighing 25 kg had a fracture in the hindlimb digits. The sheep was treated with hypoxia MSC secretome injection thoroughly at the wound area. MSCs were isolated from the umbilical cord and cultured. The cell culture was conditioned in a hypoxic environment (1 – 5% O2). Results: The results showed that secretome application significantly accelerated the fracture wound healing process. Conclusion: This finding indicates that the hypoxia UC-MSC secretome has the potential as a non-cellular regenerative approach in animal orthopaedic cases.